2018
DOI: 10.1108/nfs-05-2018-0130
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and food pattern of adolescents

Abstract: Purpose The purpose of this paper is to evaluate anthropometric data, body composition and food intake of teenagers. Design/methodology/approach This paper involves a cross-sectional study with 132 teenagers aged 15 to 19 years old from a public school of Minas Gerais, Brazil. Anthropometric measurements, body composition, food intake and sport practice were obtained. The authors performed Student’s t-test, X2 or Fisher’s exact tests and Pearson’s correlation to evaluate anthropometric variables, nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The general nutritional status of girls was better than that of boys. Previato and Behrens, 2018 also reported a high prevalence of malnutrition among boys than girls. This could be due to the fact that boys at this age are more physically active and that they tend to lose more of their body fat reserves than their counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…The general nutritional status of girls was better than that of boys. Previato and Behrens, 2018 also reported a high prevalence of malnutrition among boys than girls. This could be due to the fact that boys at this age are more physically active and that they tend to lose more of their body fat reserves than their counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…Diet plays a crucial role in ensuring the optimum growth and development of the adolescent population. Inadequacies in food and nutrient intakes can lead to impaired bodily functions and a higher risk of acquiring chronic non-communicable diseases [ 12 ], as well as viral, helminthic, parasitic, and malarial infections, especially among those in developing countries [ 3 , 13 ]. In a relevant study, the nutrient intakes of Filipino adolescents were shown to be inadequate in energy, fat, and key micronutrients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of each single nutrient may be too small to be detected, while there may be significant links between dietary patterns and the risk of obesity (Salehi-Abargouei et al, 2016). Eating habits are crucial factors that affects the risk of obesity, as several studies have demonstrated the statistical links between obesity and the low consumption of fruits, vegetables and dairy products (Dastgiri et al, 2006a;Dastgiri et al, 2006b;Huang et al, 2011;Rautiainen et al, 2016;So et al, 2017;Previato and Behrens, 2018).…”
Section: Introductionmentioning
confidence: 99%